Phase II trial evaluating the clinical and biologic effects of bevacizumab in unresectable hepatocellular carcinoma - Siegel, Abby B; Cohen, Emil I; Ocean, Allyson; Lehrer, Deborah; Goldenberg, Alec; Knox, Jennifer J; Chen, Helen; Clark-Garvey, Sean; Weinberg, Alan; Mandeli, John; Christos, Paul; Mazumdar, Madhu; et al. (Journal of clinical oncology, 2008)
To determine the clinical and biologic effects of bevacizumab, an anti-vascular endothelial growth factor (VEGF) monoclonal antibody, in unresectable hepatocellular carcinoma (HCC). Adults with organ-confined HCC, Eastern Cooperative Oncology Group performance status of 0 to 2, and compensated liver disease were eligible. Patients received bevacizumab 5 mg/kg (n = 12) or 10 mg/kg (n = 34) every 2 weeks until disease progression or treatment-limiting toxicity. The primary objective was to determine whether bevacizumab improved the 6-month progression-free survival (PFS) rate from 40% to 60%. Secondary end points included determining the effects of bevacizumab on arterial enhancement and on plasma cytokine levels and the capacity of patients' plasma to support angiogenesis via an in vitro assay. The study included 46 patients, of whom six had objective responses (13%; 95% CI, 3% to 23%), and 65% were progression free at 6 months. Median PFS time was 6.9 months (95% CI, 6.5 to 9.1 months); overall survival rate was 53% at 1 year, 28% at 2 years, and 23% at 3 years. Grade 3 to 4 adverse events included hypertension (15%) and thrombosis (6%, including 4% with arterial thrombosis). Grade 3 or higher hemorrhage occurred in 11% of patients, including one fatal variceal bleed. Bevacizumab was associated with significant reductions in tumor enhancement by dynamic contrast-enhanced magnetic resonance imaging and reductions in circulating VEGF-A and stromal-derived factor-1 levels. Functional angiogenic activity was associated with VEGF-A levels in patient plasma. We observed significant clinical and biologic activity for bevacizumab in nonmetastatic HCC and achieved the primary study end point. Serious bleeding complications occurred in 11% of patients. Further evaluation is warranted in carefully selected patients.